Ustawowy zakaz palenia wyrobów tytoniowych - Balwicka-Szczyrba, Małgorzata; Balwicki, Łukasz (Kwartalnik Prawa Publicznego, 2012)
The purpose of the article is to analyse the legal aspects of the smoking ban in statutory law, which is recognized as a main legal tool aiming at protection against harmful consequences of smoking. A special emphasis was put on the analysis of legal instruments concerning the non-smoking areas. In doing so the relevant provisions of Polish Law, especially of the Act of 9th November 1995 concerning the Health Protection Against Consequences of Tobacco Smoking were analyzed, as well as provisions of WHO Framework Convention on Tobacco Control of 21st May 2003. The Authors deal with historical development of legal regulations concerning smokingfree areas, interpretation difficulties with regard to current legal regulations as well as some questions concerning the conformity of Polish Law with the WHO Framework Convention.